Differential Diagnosis of an Elderly Manic-Depressive Patient with Depersonalization and Other Symptoms - Shigehiro Ogata; Yu Itohiya; Yuri Sakamoto; Yuki Sato; Yudai Suyama; Hidenori Atsuta; Ken Iwata (Case Reports in Psychiatry)
The case study of an elderly man having persecutory delusions and bizarre complaints at the first psychiatric interview is reported. The patient complained: “I have no sense of time” and “I have no sense of money.” He refused nursing care. He had delusions centered on himself including that of his own death, which were difficult to diagnose but suggested the possibility of Cotard’s syndrome. We assumed that the man was depressed and treated him for depression. However, as a result of this treatment he became temporarily manic but finally recovered completely. After his recovery, we learnt the patient’s past history of hospitalization for psychiatric problems, and based on that history he was diagnosed as suffering from a bipolar I disorder. The lack of typical symptoms of depression and the remarkable depersonalization and derealization in this patient made it difficult to infer a depressive state. Nevertheless, being attentive to his strange feelings related to the flow of time would have helped us to make an accurate diagnosis earlier.